Field-Based and Lab-Based Assisted Jumping: Unveiling the Testing and Training Implications - Tufano, James J.; Malecek, Jan; Steffl, Michal; Stastny, Petr; Hojka, Vladimir; Vetrovsky, Tomas (Frontiers in Physiology, 2018)
Purpose: Assisted jumping can supplement resistance training and traditional plyometric training to increase vertical jump performance. However, as coaches may choose to make field-based decisions based on lab-based research, this study determined whether a field-based assisted jumping set-up results in different ground contact times (CT), take off forces (TOF), flight times (FT), and impact forces (IF) compared to a lab-based set-up. Methods: 18 active males (24.8 ± 3.0 yr; 178.8 ± 7.8 cm; 77.8 ± 7.8 kg) performed two sessions of assisted jumping: one with each hand holding a commercially available resistance band (1m) that was attached to a pull-up bar (FIELD), and the other with assistance from a custom-built system of ropes, pulleys, and long (3m) elastic bands (LAB). With each set-up, subjects performed 5 sets of 5 countermovement jumps on a force plate. Each set was performed with either bodyweight (BW), 90%, 80%, 70%, or 60% of BW, which was achieved by either grabbing higher or lower on the bands during FIELD, or by being pulled upward via a full-body harness during LAB. The order of each visit was counter-balanced, and the order of jumps within each visit was quasi-randomized. Data from the 90%, 80%, 70%, and 60% trials for each set-up were then expressed relative to the data of BW jumps, and these relative values were then used for analysis. Results: CTFIELD was less than CTLAB at 80%, 70%, and 60%. FTFIELD was greater than FTLAB at 90% and 80%, but FTLAB became greater at 60%. TOF and IF remained unchanged during LAB, but TOFFIELD was consistently less than TOF during BW, with IFFIELD generally being greater than IFLAB. Conclusions: If the purpose of assisted jumping is to spend less time on the ground without decreasing force, systems with finite adjustments and longer bands like LAB should be used. However, shorter bands similar to FIELD may also be used; but due to the larger variability of assistance throughout the range of motion, such systems may alter the neuromuscular characteristics of the jump in other ways that should be investigated in future research.